2017
DOI: 10.1289/ehp266
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Deploying Inhaler Sensors to Identify the Impacts of Environmental Triggers and Built Environment Factors on Asthma Short-Acting Bronchodilator Use

Abstract: Background:Epidemiological asthma research has relied upon self-reported symptoms or healthcare utilization data, and used the residential address as the primary location for exposure. These data sources can be temporally limited, spatially aggregated, subjective, and burdensome for the patient to collect.Objectives:First, we aimed to test the feasibility of collecting rescue inhaler use data in space–time using electronic sensors. Second, we aimed to evaluate whether these data have the potential to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…For example, D’Arcy et al 30 developed a Bluetooth inhaler device that used acoustic recordings of inhaler usage to monitor temporal and technique adherence and assess the correlation between clinical outcomes and adherence. Furthermore, studies using the US Food and Drug Administration (FDA)-approved Propellor Health (Madison, WI, USA) digital platform and inhalers demonstrated the feasibility of tracking inhaler usage and triggers 3134 . Moreover, individuals randomized to the Propeller Health arm had more significant reductions in inhaler usage than those under routine care 35 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, D’Arcy et al 30 developed a Bluetooth inhaler device that used acoustic recordings of inhaler usage to monitor temporal and technique adherence and assess the correlation between clinical outcomes and adherence. Furthermore, studies using the US Food and Drug Administration (FDA)-approved Propellor Health (Madison, WI, USA) digital platform and inhalers demonstrated the feasibility of tracking inhaler usage and triggers 3134 . Moreover, individuals randomized to the Propeller Health arm had more significant reductions in inhaler usage than those under routine care 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In this pilot study, we demonstrated that (1) a remote inhaler sensor can monitor albuterol inhaler use in older patients with COPD and is associated with high satisfaction, (2) increased albuterol use captured by the sensor was associated with self-reported episodes of moderate-to-severe exacerbations, yet (3) large variation was seen in the daily use of albuterol in this population even in nonexacerbation days. Prior studies have used this inhaler sensor to monitor inhaler use for asthma patients (3) ; however, to our knowledge, this is the first study reporting the use of inhaler sensors in COPD patients during exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…There are several Food and Drug Administration (FDA) cleared sensor devices, which attach to the pressurized meter-dose inhalers (MDIs) and additional models that fit to different types of inhalers. (1) Electronic sensors were shown to accurately capture inhaler actuations over a 6-month period (2,3) and their use was demonstrated to improve medication adherence (4,5) and symptom control (6,7) in asthma patients. However, benefit and acceptability of these devices were tested mainly in younger asthma patients.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is strongly recommended that healthcare professionals dedicate time for device education in their clinics and review inhalation technique at each patient visit 70 . With the aim to facilitate this guidance, the evidence or lack thereof underlying ten common 'inhaler lores' beliefs, has been recently reviewed in a practical consensus statement by a panel of experts, on the basis of their combined clinical and research expertise 71 .…”
Section: Prescribe Chosen Devicementioning
confidence: 99%